2020
DOI: 10.1001/jamacardio.2019.5963
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Implanted Cardiac Rhythm Recorders With Electrocardiographic Monitoring for Detecting Arrhythmias in Pregnant Women With Symptomatic Arrhythmia and/or Structural Heart Disease

Abstract: IMPORTANCEArrhythmias are an important cause of maternal morbidity and mortality but remain difficult to diagnose. OBJECTIVE To compare implantable loop recorder (ILR) plus 24-hour Holter electrocardiographic (ECG) monitoring with standard 24-hour Holter ECG monitoring alone in terms of acceptability, ability to identify significant arrythmias, and effect on management and pregnancy outcome in women who were symptomatic or at high risk of arrythmia because of underlying structural heart disease. DESIGN, SETTIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Women in WHO class II should be assessed during each trimester and those in class III assessed monthly or bi‐monthly. A recent randomized study on the effectiveness of implanted cardiac rhythm recorders for detecting arrhythmias in pregnant women with structural heart disease suggests that those devices could be considered in HCM facilitating early detection of arrythmia or re‐assurance of the mother and avoiding harm‐full medication 3,50 . Beta‐blockers should be continued if they are already being taken and foetal growth monitored.…”
Section: Specific Cardiomyopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Women in WHO class II should be assessed during each trimester and those in class III assessed monthly or bi‐monthly. A recent randomized study on the effectiveness of implanted cardiac rhythm recorders for detecting arrhythmias in pregnant women with structural heart disease suggests that those devices could be considered in HCM facilitating early detection of arrythmia or re‐assurance of the mother and avoiding harm‐full medication 3,50 . Beta‐blockers should be continued if they are already being taken and foetal growth monitored.…”
Section: Specific Cardiomyopathiesmentioning
confidence: 99%
“…A recent randomized study on the effectiveness of implanted cardiac rhythm recorders for detecting arrhythmias in pregnant women with structural heart disease suggests that those devices could be considered in HCM facilitating early detection of arrythmia or re-assurance of the mother and avoiding harm-full medication. 3,50 Beta-blockers should be continued if they are already being taken and foetal growth monitored. Beta-blockers should be started when new symptoms occur, for rate control in atrial fibrillation and to suppress ventricular arrhythmias, with verapamil as a second choice.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…Of these patients, 8 also had permanent implantable cardioverter-defibrillators inserted . These data show that patients with peripartum cardiomyopathy remain at high risk of arrhythmias for prolonged periods and could see considerable benefit from monitoring as described by Sliwa et al…”
mentioning
confidence: 68%
“…To the Editor We congratulate Sliwa et al for their excellent analysis on the use of implantable loop recorders (ILRs) in addition to 24-hour Holter electrocardiography to improve the detection of arrhythmias in pregnant women with cardiovascular disease compared with 24-hour Holter electrocardiography alone. We believe these findings to be pertinent, as a 2019 study by Moulig et al observed 66 patients with peripartum cardiomyopathy over 5 years and found that 17% had arrhythmias, including paroxysmal supraventricular tachycardia, ventricular tachycardia, or ventricular fibrillation.…”
mentioning
confidence: 99%
“…Mittels ambulanter Langzeit-EKG-oder neuerdings intensivierter "Smart-Watch"-EKG-Aufzeichnungen sollte versucht werden, eine Korrelation zwischen Beschwerden und Rhythmusstörungen zu erzielen. In einer Vergleichsstudie an 40 Schwangeren mit Palpitationen und/oder struktureller Herzerkrankung konnten mittels Langzeit-EKG-Dokumentation bei 13-24 % Rhythmusstörungen detektiert werden, während ein implantierter Ereignisrekorder bei 9 von 17 Patientinnen (53 %) Rhythmusstörungen aufzeichnete [7]. In Einzelfällen kann eine kardiale MRT-Diagnostik sinnvoll sein, wobei Gadolinium in der Schwangerschaft vermieden werden sollte.…”
Section: Management Von Spezifischen Rhythmusstörungen In Der Schwangunclassified